'I'd (still) rather be a cyborg': The artisanal dispositif and the return of the (domestic) goddess. (July 2020) - Luckman, Susan; Phillipov, Michelle
This article identifies the rise of a series of tropes around authenticity, retreat and celebration of the artisanal as they manifest around the growing popularity of cooking and craft as activities that have become vehicles for a larger reimagining of ideal middle-class modes of living across much of the Global North. Through media examples of cooking and craft that valorise nostalgia and 'dropping out', and following McRobbie's work on the creativity dispositif, we argue that these cultural practices are united by an artisanal dispositif that fetishises the 'traditional' in a context of intensified mediatisation. We revisit Haraway's iconic text – 'A cyborg manifesto' – to identify what is at stake in the 'return' of the artisanal and its ongoing tensions between the technological and the traditional. We argue that rather than retreat, to quote more recent work by Haraway we need to 'stay with the trouble' in all its complexity.